2014
DOI: 10.1016/j.drugpo.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

“In their perception we are addicts”: Social vulnerabilities and sources of support for men released from drug treatment centers in Vietnam

Abstract: Background Amid the global transition to treat opioid addiction as an illness, many people who inject drugs (PWID) face heterogeneous legal environments that include both punitive and harm reduction measures. In Vietnam, many PWID, who have a high burden of HIV, are sent to drug treatment centers, or “06 centers”, for compulsory detoxification, vocational training, and labor for up to four years. This study investigates the challenges and facilitators of reentry into community and family life among men who are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 21 publications
2
55
0
Order By: Relevance
“…The first source is data from five studies within the Seek Test Treat and Retain (STTR) consortium funded by the National Institute of Drug Abuse(Chandler et al, 2015). The 5 studies included in these analyses were selected based on simultaneous collection of both adherence measures (described below) and were grouped into categories based on their study populations: criminal justice (CJ) (Carda-Auten et al, 2014; Gordon, Kinlock, McKenzie, Wilson, & Rich, 2013), international (Tomori et al, 2014; Wechsberg et al, 2014), or other vulnerable populations (VP) (Glenn et al, In press ). The second data source is the University of Washington site of the Centers for AIDS Research (CFAR) Network of Integrated Clinical Systems (CNICS)(Kitahata et al, 2008) cohort, a longitudinal observational study of PLWH in primary care.…”
Section: Methodsmentioning
confidence: 99%
“…The first source is data from five studies within the Seek Test Treat and Retain (STTR) consortium funded by the National Institute of Drug Abuse(Chandler et al, 2015). The 5 studies included in these analyses were selected based on simultaneous collection of both adherence measures (described below) and were grouped into categories based on their study populations: criminal justice (CJ) (Carda-Auten et al, 2014; Gordon, Kinlock, McKenzie, Wilson, & Rich, 2013), international (Tomori et al, 2014; Wechsberg et al, 2014), or other vulnerable populations (VP) (Glenn et al, In press ). The second data source is the University of Washington site of the Centers for AIDS Research (CFAR) Network of Integrated Clinical Systems (CNICS)(Kitahata et al, 2008) cohort, a longitudinal observational study of PLWH in primary care.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, strengthening the collaboration between mental health outreach teams and police departments (Girard et al, 2014) can mitigate some systemic and structural factors that cause or exacerbate mental distress such as frequent arrests and incarceration. The long-term goal should be to move from institutional to family-centered and community-based mental health services (Tomori et al, 2014), and in this context, outside of rehabilitation centers. Our findings demonstrate a clear link between past treatment at rehabilitation centers and higher levels of psychological distress.…”
Section: Social Determinants Modelmentioning
confidence: 99%
“…Social and family support are very important for drug addicts to achieve abstinence from opioid addiction. It was reported that patients who had relatives on methadone treatment had a higher retention rate, thus indicating that family ties have a huge influence on individuals' drug use behaviors 27 . The MMT program in CCSC incorporated psychosocial interventions such as group and family counseling to improve the retention rate among opioid abusers.…”
Section: Voluntary Termination Factorsmentioning
confidence: 99%